Influence of climate and climate anomalies on Norway spruce tree-ring growth at different altitudes and on glacier responses: examples from the Central Italian Alps - G. Leonelli; M. Pelfini (Geografiska Annaler: Series A, Physical Geography, 2008)
Climate change and climate anomalies are inducing strong variations in the highmountain environment, driving the responses of physical and biological systems differently. This paper assesses tree-ring growth responses to climate for two Norway spruce (Picea abies (L.) Karst.) sites at different altitudes from an Ortles- Cevedale Group (OCG; internal zones of the Central Italian Alps) valley site and reports some examples of climate impact on glacier dynamics in the OCG in recent decades. Growth–climate relationships between tree-ring chronologies and meteorological data were established by means of Pearson’s correlation and response functions. In the high-altitude chronology we found a strong signal of July temperatures, whereas the low-altitude chronology also contained a signal of summer precipitation. Climate anomalies occurring in these months proved to influence tree growth at the two sites differently. In summer 2003 extreme climatic conditions established over Europe and the Alps, strongly affecting physical and biological systems. Spruce responses to the climate anomaly of 2003 were more evident with a one-year lag. The high-altitude site profited from the warmer growing season, whereas trees at the low-altitude site experienced water stress conditions and their growth was strongly inhibited also in the following year. Glacier mass loss in the OCG in 2003 was the highest since yearly measurement started. The examples reported confirm the strong and even divergent variations affecting the Alpine environment, induced by recent climate change.